PENGARUH PROFITABILITAS, PAJAK, PERTUMBUHAN PERUSAHAAN DAN KEBIJAKAN DIVIDEN TERHADAP KEPUTUSAN PENDANAAN - Devi Kurnia Astuti, 13.05.52.0042; Wahyudi, Djoko (Students Journal of Accounting and Banking, 2017)
The funding decision is the decision of the company in determining the source of funding. Decisions taken managers in spending should be considered carefully on the source of funds that will be selected for each source of funds have different financial consequences. The funding decision is influenced by many factors, including the profitability, tax, corporate growth, and dividend policy. This study aimed to examine the effect of profitability, Tax, Company Growth and Dividend Policy on Funding Decisions on manufacturing companies listed in Indonesia Stock Exchange Year 2012-2014. The population in this research is manufacturing companies listed in Indonesia Stock Exchange in 2012-2014. The sampling technique was conducted by purposive sampling. Purposive sampling based company gained as much as 127 before and after the outlier in the outlier as many as 115 companies sampled for 3 years. Data analysis technique used is the classical assumption test and multiple linear regression analysis using SPSS 19. The results of this study simultaneously profitability, tax, corporate growth and dividend policy influence on funding decisions. While partially shows that the profitability and dividend policy significant negative effect on Funding Decisions. Taxes and no effect on the companys growth Funding Decisions.Keywords:Â Profitability, Tax, Corporate Growth, Dividend Policy and Funding Decisions